Qualitative Study on the Implementation of Visual Projector Media in Students' Learning Motivation - Imanuela, Putri; Setiawan, Deni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to analyze the implementation of LCD projector media in learning and its effect on the learning motivation of fourth grade students of Wonolopo 03 State Elementary School. The research method used is a qualitative approach with a field study design (field research). Data collection was conducted through in-depth interviews with teachers and students and direct observation in learning activities by studying the interaction patterns of students and teachers to understand the impact of using LCD projectors on student engagement and understanding. The results showed that the use of LCD projectors increased students' learning motivation, focus, and active participation in the learning process. Visualization of material through images and videos makes it easier for students to understand the concepts taught compared to the conventional lecture method. In addition, students showed higher involvement in discussions and had the initiative to seek additional information outside the classroom. However, this study also identified some obstacles in implementation, such as power outages and limited technical skills in using the devices. Therefore, infrastructure optimization as well as training for teachers and students are needed to make the use of LCD projectors more effective and sustainable in improving the quality of learning.